Enhancing Urban Water Resilience Awareness through Interactive Geospatial Learning - Arief Nasrudin; Tito Latif Indra; Margaretha Hanita; Abdul Rivai Ras (Online Learning In Educational Research (OLER), 2026)
Urban water resilience has become an essential component of environmental education, yet students often struggle to understand the complex relationships among hydrological processes, spatial vulnerability, and mitigation strategies using conventional instructional media. This study investigated the effectiveness of interactive geospatial learning in enhancing students’ urban water resilience awareness. A quasi-experimental pretest–posttest control group design was conducted with 120 eleventh-grade students from two intact classes in Jakarta. Students in the experimental group learned through an interactive geospatial platform that enabled exploration of hydrological layers, spatial risk visualization, and scenario-based environmental analysis, whereas the control group received conventional instruction using static visual materials. Urban water resilience awareness was assessed using a situational judgment test measuring hydrological understanding, spatial vulnerability, and mitigation decision-making. The findings indicate that students who learned with interactive geospatial media demonstrated substantially greater improvement than those receiving conventional instruction. Most students in the experimental group achieved high levels of learning improvement and successfully met the expected learning mastery criteria. These findings suggest that interactive geospatial learning provides an effective technology-enhanced approach for strengthening spatial reasoning, environmental literacy, and urban water resilience awareness in secondary education.